Challenges, Risks and Opportunities for Connected Vehicle Services in Smart Cities and Communities - Yorgos, Yorgos J.Stephanedes; Golias, Mihalis; Dedes, George; Douligeris, Christos; Mishra, Sabyasachee (My University, 2019)
A multi-level multi-objective framework is proposed for identification and management of risk for connected vehicle services in smart cities and communities. The framework will better model uncertainty, interdependencies, priorities between objectives and players as single-level multi-objective optimization is insufficient to tackle the complexities of a smart city ecosystem. An approach for determining an index for city readiness for connected and autonomous vehicles across the domains of smart connected cities is also proposed. A risk management process for smart port cities is introduced, focusing on coordinating complex subsystems of port and near-port areas. The process is based on analyzing risk of potential hazards to better comprehend their nature and need for prevention strategies.
Keywords: Smart cities; risk management; connected vehicles; ITS; C-ITS; STPA